Analisis Sengketa Pajak Pertambahan Nilai Atas Non Funded Income Pada Pengusaha Jasa Perbankan - Agus Suharsono (Universitas Katolik Soegijapranata, Semarang, 2021)
This study analyzes Value Added Tax disputes on Non-Funded Income at Banking Service Entrepreneurs with a case study of the Supreme Court Reconsideration Decision Number 628/B/PK/PJK/2019 to find out how the Judge decided the dispute. The research method used is juridical normative with statutory, case, and analytical approaches. The data used are laws, Judges' Decisions, and Doctrine. The data were collected by means of document studies, the results of data processing were narrated descriptively with the IREAC law application model: Issues, Rules, Evidence, Application, Conclusion. The results of the research are the tax authorities' opinion that the Selling Agent Fee-Invest Services-Services Priority account as the name implies is income from sales agent service fees as Non-Funded Income which is an object of VAT, Judges based on the evidence in court argued that the account was for banking services that were not objects VAT. In determining taxes, tax authorities are based on formal principles, while judges are based on material principles or the principle of substance over the form. Judges' decisions that are legally enforceable are still a material source of law, and should be used as a consideration for the tax authorities in determining taxes for similar cases so that they do not become tax disputes that must be resolved through acting legal measures that require time, effort and other resources.